2022
DOI: 10.4240/wjgs.v14.i8.788
|View full text |Cite
|
Sign up to set email alerts
|

Model established based on blood markers predicts overall survival in patients after radical resection of types II and III adenocarcinoma of the esophagogastric junction

Abstract: BACKGROUND In recent years, the incidence of types II and III adenocarcinoma of the esophagogastric junction (AEG) has shown an obvious upward trend worldwide. The prognostic prediction after radical resection of AEG has not been well established. AIM To establish a prognostic model for AEG (types II and III) based on routine markers. METHODS A total of 355 patients who underwent curative AEG at The First Affiliated Hospital of Anhui Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Third, the published nomograms by other researchers were mostly aimed at advanced EJA patients who only received chemoradiotherapy 21 , 24 . Indeed, two studies have constructed nomograms using other indicators for EJA patients receiving curative surgery resection with the C-indexes of 0.76 and 0.69 11 , 30 , which were consistent with our results. Importantly, our results could be more solid as we analyzed in a large sample size with validation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Third, the published nomograms by other researchers were mostly aimed at advanced EJA patients who only received chemoradiotherapy 21 , 24 . Indeed, two studies have constructed nomograms using other indicators for EJA patients receiving curative surgery resection with the C-indexes of 0.76 and 0.69 11 , 30 , which were consistent with our results. Importantly, our results could be more solid as we analyzed in a large sample size with validation.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing numbers of publications showed that some newly-constructed nomograms could provide a more precise prognosis prediction than the traditional cancer TNM system 9 , 10 . Wei et al have constructed a novel nomogram in EJA patients who underwent curative resection containing TNM staging system, body mass index (BMI) and neutrophil-to-lymphocyte ratio (NLR), which showed better discrimination and calibration ability compared with TNM system 11 . However, validation was lacking in their study.…”
Section: Introductionmentioning
confidence: 99%